Body composition and functional correlates of CF youth experiencing pulmonary exacerbation and recovery. Issue 2 (3rd November 2022) - Boat, Thomas; Hente, Elizabeth; Hardie, William; Szczesniak, Rhonda; Gecili, Emrah; Zhou, Grace; Taylor, Jacqueline; Amin, Raouf
Abstract: Background: Youth with cystic fibrosis (CF) and pulmonary exacerbation (PEx) often experience weight loss, then rapid weight gain. Little is known about body composition and its relationship to functional outcomes during this critical period. Methods: Twenty CF youth experiencing PEx were assessed on the day following admission and 7–17 days later at discharge for body mass index (BMI), fat mass index (FMI), lean mass index (LMI), skeletal muscle mass index (SMMI), and functional measures: percent predicted forced expiratory volume in 1 second (FEV1) (ppFEV1), maximal inspiratory and expiratory pressures (MIPs and MEPs), and handgrip strength (HGS). Changes from admission to discharge and correlations among body composition indices and functional measures at both times are reported. Results: Upon admission, participant BMI percentile and ppFEV1 varied from 2 to 97 and 29 to 113, respectively. Thirteen had an LMI below the 25th percentile and nine had a percent body fat above the 75th percentile. BMI and FMI increased significantly ( p  = 0.03, 0.003) during hospitalization. LMI and SMMI did not change. FEV1 and MIPS increased ( p  = 0.0003, 0.007), independent of weight gain, during treatment. HGS did not improve. Conclusions: Many youth with CF, independent of BMI, frequently carried a small muscle mass and disproportionate fat at the time of PEx. During hospital treatment, weight gain largely represented fat deposition; muscle mass and strength did not improve. A need for trials of interventions designed to augment muscle mass and function, and limit fat mass accretion, at the time of PEx is suggested by these observations.